Systematic review exploring human, AI, and hybrid health coaching in digital health interventions: trends, engagement, and lifestyle outcomes - Loughnane, Croía; Laiti, Justin; O’Donovan, Róisín; Dunne, Pádraic J. (Frontiers in Digital Health, 2025)
IntroductionDigital Health Interventions (DHIs) have been identified as a solution to the United Nations Sustainable Development Goals (SDG3) for health promotion and prevention. However, DHIs face criticism for shallow and transactional engagement and retention challenges. Integrating DHIs with health coaching represents a promising solution that might address these issues by combining the scalable and accessible nature of DHIs with the meaningful and engaging nature of health coaching. This systematic review aims to synthesise existing peer-reviewed research on coach-facilitated DHIs to understand how digital health coaching is being used in DHIs and the impact it has on engagement and lifestyle outcomes.MethodsStudies examining DHIs with a coaching component addressing lifestyle outcomes were included. A search of APA PsychINFO, Medline, Web of Science, and Scopus was performed from inception to February 2025. Three authors conducted the study selection, quality appraisal using the Mixed Methods Appraisal Tool (MMAT), and data extraction. Data extraction captured study characteristics, coaching features, participant engagement, and lifestyle outcomes.ResultsThirty-five studies were identified and synthesised using a narrative synthesis approach. This review highlights three coaching modalities in DHIs: digital human coaching, Artificial Intelligence (AI) coaching, and hybrid (human-AI) coaching. All coaching modalities demonstrated feasibility and acceptability.DiscussionWhile both human and AI coaching have shown a positive impact on both engagement and lifestyle outcomes, hybrid approaches need further refinement to harness AI's scalability and the depth of human coaching. However, the variability of engagement metrics and coaching protocols limited study comparability. Standardising how engagement and coaching delivery are measured and contextualised is crucial for advancing evidence-based digital health coaching. This review followed PRISMA guidelines and was registered in PROSPERO (Registration number: CRD42022363279). The Irish Research Council supported this work.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022363279, identifier: CRD42022363279.